Directional ionic transport across the oxide interface enables low-temperature epitaxy of rutile TiO2 - Yunkyu Park (Nature Portfolio, 2020)
The research to utilize chemical potential mismatch for materials synthesis has been limited across the oxide interface. Here, the authors show that directional ionic transport from the VO2 layers stabilizes the rutile TiO2 phase at extremely low temperatures, at which epitaxy is difficult, by effectively lowering the activation barrier for crystallization.